A novel L12-strengthened multicomponent Co-rich high-entropy alloy with both high γ′-solvus temperature and superior high-temperature strength. (1st July 2021) - Cao, B.X.; Kong, H.J.; Ding, Z.Y.; Wu, S.W.; Luan, J.H.; Jiao, Z.B.; Lu, J.; Liu, C.T.; Yang, T.
Abstract: A L12 -strengthened multicomponent Co-rich high-entropy alloy with superior microstructural stability was developed in this study. High-density cuboidal γ′ particles were found to embed in the matrix for the alloy subjected to isothermal aging at temperatures ranging from 800 to 1100 °C without the formation of brittle intermetallic phases neither at grain boundaries nor grain interior after long-term thermal exposure. Atom probe analyses indicated that Ta and Nb elements preferentially partitioned to the γ′ intermetallic phase, which is found to be substantially important for stabilizing the L12 ordered crystalline structure. More importantly, the present alloy exhibited a good combination of both high γ′-solvus temperature (1125°C) and low mass density (8.28 g cm −3 ), together with superb high-temperature tensile strength (755 MPa at 800 °C and 664 MPa at 900 °C). The present findings offer an essential paradigm for designing advanced L12 -strengthened high-temperature alloys with broader temperature capabilities based on Co. Graphical abstract: Image, graphical abstract